ADVANTAGES OF DISTANCE LEARNING STYLE IN THE EDUCATIONAL SYSTEM - Kayumov Xasanturdi Absolomovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Distance learning style is a new form of correspondence learning. Distance learning is independent learning. Independent reading develops a person's abilities to think independently, assess state, draw conclusions and predict.